Communicating hip-hop : how hip-hop culture shapes popular culture - Sciullo, Nick J. (Praeger, an imprint of ABC-CLIO, LLC, 2019)
This book considers hip-hop's role in shaping a number of different aspects of modern culture ranging from law to communication and from business to English studies.